IMPLEMENTASI SMALL CLAIM COURT DAN IMPLIKASINYA TERHADAP ASAS PERADILAN SEDERHANA, CEPAT, DAN BIAYA RINGAN - ,, Yevendri (Fakultas Hukum Universitas Tamansiswa Padang, 2022)
Simple, fast, and low-cost justice is a necessity in the dynamics of law in Indonesia. One of the efforts made by the Supreme Court in realizing this principle is to enforce PERMA Number 2 of 2015 in conjunction with PERMA Number 4 of 2019 concerning Procedures for Settlement of Simple Lawsuits. The Class IA Padang District Court as one of the first- level courts within the scope of general judicial authority in accordance with its function as a place for law enforcement and justice is required to implement PERMA Number 2 of 2015 in conjunction with PERMA Number 4 of 2019 concerning Procedures for Settlement of Simple Lawsuits. Departing from the background, this thesis is entitled: Application of a Simple Claim (Small Claim Court) and its Implications on the Principles of a Simple, Fast, and Low Cost Justice (Study at the Padang Class IA District Court) with the formulation of the problem: how is the application of a simple lawsuit (Small Claim) Court) and implications for the principle of a simple, fast and low cost trial in the Padang Class 1A District Court?. In answering the problem, a sociological juridical approach is used, secondary data is collected through literature searches, documents, and primary data through interviews with the Deputy Chief Justice, Judge, and Junior Civil Registrar of the Padang Class 1A District Court. The data is processed using computer facilities, carrying out data entry, editing, data tabulating or tabulating activities, finally, qualitatively analyzed. The conclusion obtained is that the application of a simple lawsuit in the Padang Class 1A District Court refers to PERMA Number 2 of 2015 in conjunction with PERMA Number 4 of 2019 concerning Procedures for Settlement of Simple Lawsuits. The application of this simple lawsuit in turn resulted in not all civil cases registered with the Padang Class 1A District Court being resolved through the ordinary examination procedure but also resolved through a simple lawsuit examination procedure. Meanwhile, the implication for the principle of fast, short, and low-cost trial at the Padang Class 1A District Court is a significant reduction in the pile of civil cases that have been a heavy workload for judges. The costs incurred are no longer large or high because the time spent in civil cases in a simple lawsuit does not take long, which is only 25 days and the case examination is not complicated, clear and uncomplicated.